Susceptibility to organophosphate insecticides in Aedes aegypti (Diptera: Culicidae) from northern Colombia and associated resistance mechanisms - María Claudia Atencia-Pineda; Javier García-Leal; Diana Diaz-Ortiz; Paula Pareja-Loaiza; Lisandro Pacheco-Lugo; Richard Hoyos-López; Alfonso Calderón-Rangel; Pedro Fragozo-Castilla; Selene M. Gutiérrez-Rodríguez; Adriana E. Flores; Ronald Maestre-Serrano (Parasites & Vectors)
Abstract Background Aedes aegypti is the primary vector of dengue, chikungunya, and Zika viruses in Colombia. Various insecticides, including pyrethroid, organophosphate, and carbamate insecticides; growth regulators; and biological insecticides, such as Bacillus thuringiensis var. israelensis, have been used to control Ae. aegypti populations. However, organophosphates such as malathion, pirimiphos-methyl, and temephos have been used over the last decade owing to the high resistance to pyrethroids. Methods This study assessed the susceptibility to organophosphates in 14 Ae. aegypti populations from the Córdoba department in northern Colombia. Moreover, possible resistance mechanisms were investigated by determining the activity levels of α-esterases, β-esterases, mixed function oxidases (MFOs), glutathione S-transferases (GSTs), and insensitive acetylcholinesterase (iAChE). Additionally, the Ace-1 gene was sequenced to identify mutations at the target site of action. Results The populations were susceptible to temephos and malathion but resistant to fenitrothion, and in three of them, to pirimiphos-methyl. Alterations in the enzyme activity levels of α-esterases and β-esterases, GST, and iAChE were observed among the populations, with high enzyme activity levels of α and β esterases associated with resistance to fenitrothion. No mutations were identified in the Ace-1 gene. Conclusions These findings are highly relevant for vector control programs in the region, as they allow for adjustments in resistance management strategies and improve the effectiveness of interventions against these arboviruses. Graphical Abstract